High dynamic range image processing - Aloysius Adi Pratama (2013)
High Dynamic Range (HDR) image has an increasingly popular demand nowadays. A wide range of methods have been developed to achieve the best result. The development focuses on upgrading the quality of standard JPEG image into HDR. The most common approach is by combining multiple exposure images into a single image that has wide exposure range. This method requires determining which pixel should be displayed from each image. In this project, an exposure fusion method is developed. In addition, multiple images taken by handheld camera usually have a slightly shifted effect. To facilitate the multiple images fusion, an algorithm for image alignment and registration is also implemented. The alignment is performed by applying translation in horizontal and vertical axis. Besides multiple images fusion, another approach is by expanding the pixel content of a single image. As a common practice, only a single image is taken which is partially underexposed and partially overexposed. This project addresses this issue by performing expansion and tone mapping. The resulting image will be of HDR quality. In conclusion, the overall project, including the user interface, was developed using JAVA programming language. The project provides a platform for HDR imaging; as most of the basic features have already been carried out.